The association between family cohesion and disability following blunt trauma: findings from a level-I trauma center in Saudi Arabia - Sarah Mohammed Almarwani; Leen Omar Hijazi; Modhi Abdullah Alamer; Jury Muhanad Alnwaiser; Reem Abdullah Aldakheel; Khalid Alsheikh; Ibrahim Albabtain; Suliman Alghnam (BMC, 2020)
Abstract Background Injuries pose a significant burden on population health of Saudi Arabia. Even in nonfatal injuries, the burden varies from temporary to permanent disabilities. Health outcomes following injuries can vary, and predictors of recovery from disability are not well understood. In the Kingdom, family values and cohesion can differ from other countries due to several factors, including religious beliefs and cultural traditions. Learning about predictors of injury recovery can improve prevention as well as planning for rehabilitation programs. Therefore, the study aims to evaluate the association between family cohesion and recovery following blunt injuries. Methods This prospective study included 249 patients who were hospitalized for at least 1 day following blunt trauma in King Abdulaziz Medical City, Riyadh. Adult patients were interviewed twice: initially during admission, and a second interview via the phone 3 months after discharge. Baseline information included: demographics, injury characteristics, the five dimensions EQ-5D and family support scale. The follow-up interview captured only EQ-5D. Suboptimal family cohesion was defined as any issue with the relationship with parents, spouse, or siblings. Any disability was defined as a reported limitation in one or more domains of the EQ-5D scale. Logistic regression was used to assess the association between family cohesion and recovery at 3 months. Results Of the overall sample, 169 (67.8%) responded to the second interview, and three patients passed away. About 95.2% of patients reported disabilities at baseline, while 88.1% continued to report disabilities after 3 months. Forty patients (16.1%) reported suboptimal family cohesion. Of these patients, 37(94.87%) were in pain, 33(82.5%) reported problems with usual activities, 32(80%) faced problems with self-care, 32 (80%) patients had difficulty in mobility, and 23(57.5%) were depressed. Multivariable regression suggested that patients with suboptimal family cohesion were less likely to recover from disabilities. Conclusion The prevalence of any disability 3 months after discharge is striking. This study suggests that health outcomes after blunt trauma are affected by the strength of the patient's family cohesion. More research is needed to identify effective ways through which the provision of social support can reduce short term disability after trauma.